New Chinese cinemas : forms, identities, politics / edited by Nick Browne [and others]. - Browne, Nick (Cambridge University Press, 1994)
New Chinese Cinemas analyzes the changing forms and significance of filmmaking in the People's Republic, Taiwan, and Hong Kong, emphasizing the way film commented on the profound social changes that occurred in East Asia in the 1980s. These original essays offer extended analyses of the important trends, themes, and styles that define contemporary Chinese filmmaking. They demonstrate that film is an important aesthetic form and social document in the interpretation of these ongoing changes.
Keywords: Motion pictures -- China.; Motion pictures -- Taiwan.; Motion pictures -- China -- Hong Kong.; Motion pictures.; China.; China -- Hong Kong.; Taiwan.; History.; Criticism, interpretation, etc.